2013
DOI: 10.1007/s00192-013-2246-0
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic medication use for female overactive bladder in the ambulatory setting in the United States

Abstract: Annually, more than 8 million outpatient visits occur in which adult women in the United States are using an OAB anticholinergic medication. Despite the abundance of newer-generation medications, tolterodine and oxybutynin remain the most commonly prescribed anticholinergic drugs for OAB. Solifenacin is the most popular newer-generation anticholinergic drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…Most health services research studies using claims-based data sources have focused on urinary incontinence generally, rather than on OAB specifically. In one of the only studies to examine healthcare utilization for OAB, Ju et al, using data from the 2009 US National Ambulatory Medical Care Survey, estimated that US women made 8.1 million ambulatory visits (i.e., 1.6 % of all ambulatory visits) that were associated with anticholinergic OAB medications [29]. This represents an annual rate of 68 visits per 1000 women.…”
Section: Us Healthcare Resource Utilization For Oabmentioning
confidence: 99%
“…Most health services research studies using claims-based data sources have focused on urinary incontinence generally, rather than on OAB specifically. In one of the only studies to examine healthcare utilization for OAB, Ju et al, using data from the 2009 US National Ambulatory Medical Care Survey, estimated that US women made 8.1 million ambulatory visits (i.e., 1.6 % of all ambulatory visits) that were associated with anticholinergic OAB medications [29]. This represents an annual rate of 68 visits per 1000 women.…”
Section: Us Healthcare Resource Utilization For Oabmentioning
confidence: 99%
“…Whether trends in age or other prescriber demographics or changing prevalence of urinary conditions may influence Bethanechol prescription cannot be determined. Despite these limitations, the NAMCS has previously been used to identify prescription patterns of anticholinergic agents for overactive bladder and antibiotics for urinary tract infections …”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have explored trends in the use of OAB agents in different populations, however these studies have focused on describing the uptake of solifenacin and darifenacin upon their introduction to the market in North America and Sweden. [28][29][30] All of these studies demonstrated a marked increase in solifenacin and darifenacin prescribing upon their introduction to the market, but the degree to which these prescribing rates grew differed across jurisdictions. In our study, we also demonstrated that solifenacin prescribing has increased considerably, and is now the dominant OAB agent in Canada.…”
Section: Discussionmentioning
confidence: 99%